Strategi Pemasaran Pada Rafting Di Desa Kedewatan Kecamatan Ubud - Wibawa, Dewa Pranata Ari; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i01.p19, 2018)
Travel located rafting on the Ayung Rivers is a tour that is visited by tourists. This raises the more recent stand rafting companies that make the competition tighter. With the amount of competition it is very important to have a marketing strategy is right on target for Sobek rafting in order to maintain its existence. This study aims to assess the strengths and weaknesses of Sobek rafting.                        Data collected by observation, interview, and literature study. The results showed that the strength factor Sobek rafting is the quality of the guides are given already has considerable experience, adequate facilities, safety (security) in following the rafting tour of an early start to the end of the trip and Service (service), while weaknesses are of standard implementation imposed by torn to serve tourists not run properly because of a lack of supervision. A vigorous marketing is very important but also must be balanced with adequate services to maintain the confidence of tourists to come back to use the services Sobek rafting.   Keywords : Marketing Strategy, Rafting, Ayung Rivers